URETERIC ANGIOMYOLIPOMA CAUSING UNILATERAL PELVI-URETERIC JUNCTION OBSTRUCTION - Khan, Iftikhar Ali; Shahab, Durre; Rehman, Asad; Jamil, Imran; Akhter, Saeed (Journal of Ayub Medical College Abbottabad, 2015)
A 63 year old lady, presented to us with nonspecific abdominal pain. Ultrasonography (USG) and CT scan abdomen and pelvis, showed right moderate hydronephrosis, with no evidence of mass at pelvi-ureteric junction (PUJ) obstruction. Per-operatively mass upper ureter was found obstructing PUJ. Mass was excised and pyeloplasty done, with Double J (DJ) Stenting. Stent was removed after a week. Histopathology of specimen showed upper ureteric Angiomyolipoma. Keywords: Pelvi-ureteric junction obstruction, Angiomyolipoma, Unilateral Hydronephrosis